Improving Teenagers' Knowledge and Attitudes Towards Anaemia and Blood Groups Through a Comprehensive Education Programme at Dr. Soetomo High School, Surabaya - Putri Kwarta, Cityta (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Adolescence is a vital stage of development involving rapid physical and psychological changes that increase nutritional demands. Iron-deficiency anaemia is a widespread health problem among Indonesian teenagers, negatively affecting concentration, energy levels, and immune function. Equally important is adolescents’ awareness of their blood group, which is critical for emergency medical treatment but often overlooked. Education targeting these issues is necessary to improve adolescent health outcomes. Methods: This community program at SMA Dr. Soetomo Surabaya included interactive educational sessions led by health experts and university students. Various learning tools such as videos, posters, and leaflets were used. Students’ knowledge was measured using questionnaires before and after the sessions. Results: The intervention led to notable improvements in students’ understanding of anaemia’s causes, symptoms, and prevention strategies. Pre-test to post-test analysis revealed a significant increase in anaemia knowlede, with average scores improving from 60% to 85%. Awareness about blood groups (ABO and Rh) also increased, with knowledge scores rising from 55% to 80%. This was accompanied by increased motivation to adopt healthier habits and learn their blood group. Formation of student health teams and use of digital platforms supported ongoing health promotion. Conclusion: The program successfully enhanced adolescents’ knowledge and health awareness. Engaging, school-based education with peer participation can foster long-term positive behavior changes. Expansion of such programs is recommended for sustained impact.